2019
DOI: 10.1007/s10964-019-01126-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Maternal Overprotection, Adolescent Internalizing and Externalizing Problems, and Psychological Need Frustration: A Multi-Informant Study Using Response Surface Analysis

Abstract: Acknowledgments. The authors would like to thank the adolescents and parents who kindly accepted to participate in the study, as well as the master thesis students who helped in the data collection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 89 publications
(95 reference statements)
3
49
0
6
Order By: Relevance
“…Although the results showed that adolescents disclose information more frequently in responsive and autonomy supportive parenting contexts, existing measures assessing parenting that directly address adolescents’ information management (e.g., Tokić Milaković & Pećnik, 2014 ) should be more widely used. In addition, to get a complete picture of parental dimensions related to adolescent information management, future studies could also consider need-thwarting parenting (Vansteenkiste & Ryan, 2013 ), such as parental overprotection (e.g., Van Petegem et al, 2020 ). Second, for each type of strategy, we combined several items to obtain an overall frequency of use of that strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results showed that adolescents disclose information more frequently in responsive and autonomy supportive parenting contexts, existing measures assessing parenting that directly address adolescents’ information management (e.g., Tokić Milaković & Pećnik, 2014 ) should be more widely used. In addition, to get a complete picture of parental dimensions related to adolescent information management, future studies could also consider need-thwarting parenting (Vansteenkiste & Ryan, 2013 ), such as parental overprotection (e.g., Van Petegem et al, 2020 ). Second, for each type of strategy, we combined several items to obtain an overall frequency of use of that strategy.…”
Section: Discussionmentioning
confidence: 99%
“…During adolescence, such developmentally inappropriate strategies (e.g., incessantly warning about anything that could happen, interfering in adolescents' friendships, or intruding in their privacy) can threaten the resolution of fundamental developmental tasks such as identity exploration and the development of independence (Brenning, et al, 2017;Segrin, et al, 2015). Recently, several studies consistently showed that parental overprotection is associated with numerous psychosocial difficulties in adolescence and young adulthood, including lower self-esteem and internalizing problems (e.g., Schiffrin et al, 2014Schiffrin et al, , 2019Van Petegem et al, 2020;Weitkamp & Seiffge-Krenke, 2019). Research not only documented the harmful psychosocial correlates of parental overprotection throughout development, but also yielded insights regarding its determining factors (Segrin, et al 2013).…”
Section: Storm and Stress And Parental Overprotectionmentioning
confidence: 99%
“…Parental overprotection was assessed using the Multidimensional Overprotective Parenting Scale (MOPS; Kins & Soenens, 2013), which was adapted to a parent-report format (Van Petegem et al, 2020). In line with previous studies (e.g., Brenning et al, 2017), we assessed six components of overprotective parenting (premature problem solving, anxious rearing, privacy invasion, infantilization, emotional hyperactivation, and general overprotection).…”
Section: Overprotective Parentingmentioning
confidence: 99%
“…The use of interaction terms in a regression analysis (also known as polynomial regression analysis) has been suggested as an alternative in order to examine not only whether differences between reports relate to outcome variables, but whether these differences relate to the outcome in addition to main effects of individual reports (Laird and De Los Reyes 2013). Results of the retrospective studies that used this approach focused on negative aspects of parenting and indicated for instance that congruence of more negative perceptions on parenting or family functioning was related to more adolescent maladjustment (Hou et al 2019;Van Petegem et al 2019), but also that high levels of adolescents' depressive symptoms were related to incongruence of father-adolescent reports of negative interactions, with adolescents reporting high and fathers low negative interaction (Nelemans et al 2016). These results not only suggest that it is important to take into account both congruence and incongruence, but also to examine adolescent-mother and adolescent-father dyads separately.…”
Section: The Link Between Discrepancies In Parenting and Adolescent Well-beingmentioning
confidence: 99%